Vous êtes sur la page 1sur 23

 n n n n k k

 r r k k

 ∅ {} x ∈ A x A x ∈/ A x A
 A A B A = B) ⊆ B = A A B A ⊂ B B

(A)

A A B = {x | x A ou x B}.

A A B= {x | x A et x B}.

A A B= {x | x A et x / B}.

A #A #{a,

|A|

}

A

B

B

B

G V E

V (G) ou V G G

E(G) ou E G G

|G| ou n(G) G

e(G)

u v

d G (v) G v v

d(u, v)

δ(G) ou δ G G

∆(G) ou G G

Γ G (v)

Γ G (v) ∪ {v} G v

Γ G (W )

G(V, E)

G

u v

u v

G v

G W

G G = (V, E)

G

H G

G = (V (G), V (G) 2 E(G))

H G

 G − v v G G − uv uv G G ∪ v v G

 G ∪ uv uv G G ∪ H H G G + {v} v G G + {uv} uv G G + H H G
 G/xy G, xy G/A G, A

E G (U, W ) U W U W V (G)

n

n

n m n × m

E n

K n

2

= n(n1)

2

K n,m

E n

G n

G(m, n)

G[U ]

κ(G)

λ(G)

H G

C n

P n

E n = K n

G n

G m n

G U V (G)

G

G

H G

n n

n

 uv u v u v uv u uv uv u v u uv u v uv ∈ E(G) uv vw u W

G = ({u, v}, {uv}) u v

G = graphe G = (V, E) o`u E V 2

G (V, E)

V

E G = (V, E)

V E E V 2

G = G = (V, E) E V 2

V (G) = ensemble des sommets de G = V

G = (V, E) V (G) G V (G) = V V G

G = (V, E) E(G). E(G) = E E G

v = v v V (G)

 uv = uv = [u, v] ⇔ uv ∈ E(G) uv = uv = (u, v) ⇔ uv ∈ E(G)

G, u, v V (G)

u v u v uv E(G)

G,

uv vw v Γ(u) v Γ(w)

u 1 v, u 2 v,

,

n

u n v v i=1

Γ(u i